2008
DOI: 10.1177/1365480208098390
|View full text |Cite
|
Sign up to set email alerts
|

External change agents in developed and developing countries

Abstract: During the last four decades, educational researchers and practitioners have intensively engaged in bringing about positive changes in schools. Therefore, the kinds of changes introduced to schools have become complex in nature and overwhelming in number -from improving teacher professional knowledge base and teaching repertoires to developing innovative curricula to changing the organizational structures and cultures in schools. The skills required by schools and teachers to implement these changes have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Instead, they emphasized their role as coaches, who would moderate and structure existing processes through systemic feedback (Dedering et al, 2013, pp. 28-33;Tajik, 2008). Second, our findings demonstrated that the external consultants faced considerable resistance when entering the specific school contexts, in most of which, school improvement processes were already underway.…”
Section: Discussionmentioning
confidence: 75%
“…Instead, they emphasized their role as coaches, who would moderate and structure existing processes through systemic feedback (Dedering et al, 2013, pp. 28-33;Tajik, 2008). Second, our findings demonstrated that the external consultants faced considerable resistance when entering the specific school contexts, in most of which, school improvement processes were already underway.…”
Section: Discussionmentioning
confidence: 75%
“…Higher education institutions have a particularly intriguing potential for facilitating societal responses to the multiplicity of sustainability concerns that communities worldwide are confronting. Tajik (2008)…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berater*innen handeln aus verschiedenen Rollenverständnissen, z.B. als Moderator*in, kritische*r Freund*in oder als Fachkraft mit spezieller Expertise (Tajik, 2008).…”
Section: Welche Anlässe Bzw Auslöser Für Schulentwicklungsberatung Gi...unclassified